Dental enamel defects and dental caries of primary teeth among Indigenous children in Western Australia. (21st December 2022) - Arrow, P; Piggott, S; Jamieson, L; Brennan, D; Tonmukayakul, U; Kularatna, S; Atkinson, D; Nanda, S
Abstract: Background: Teeth affected with enamel defects (EDs) are at an increased risk of dental caries. In spite of improving oral health status overall in Australia, Indigenous Australians still experience higher rates of dental caries than non‐Indigenous Australians. This study reports on the prevalence of EDs and dental caries experience among Indigenous children in the Kimberley region of Western Australia. Methods: Health status of all the primary teeth (ICDAS II criteria) and the presence of EDs on index teeth (modified Dental Defects of Enamel index; DDE) of young Indigenous children who participated in a 2‐arm intervention trial was recorded. Generalized estimating equations were used to estimate the association between EDs and dental caries and effect estimates were presented as odds ratios and associated 95% confidence intervals. Results: Person‐level prevalence, from 237 children (mean age 3.6 years, standard deviation 1.7) assessed for EDs, was 58% and tooth‐level prevalence was 24%. Teeth affected with demarcated or diffuse defects were associated with a twofold higher odds of having caries experience, odds ratio (OR) 2.5, 95% confidence interval (CI) 1.7–3.7 and OR 2.7, 95% CI 1.7–4.0 respectively. Conclusions: The presence of EDs among young Indigenous children was associated with a higher odds of caries experience among affected teeth.